Agriculture by product fibre hybrid composite for use in the construction of armor articles, members, structures and the like - Yaakob, Mohd Yuhazri; Md Palil, Md Dan (2012)
The present invention relates to agriculture by product fibre hybrid composite for use in the construction of armor articles, members, structures and the like. More particularly the present invention relates to a natural composite hybrid material to be made into a hard armor protective covering which is strong, lightweight and with ballistic resistant. Most particularly the present invention relates to the construction of armor articles, members, structures and the like with sufficient thickness, filler arrangement and low cost but cost effective and easy fabrication method.